The Development of Flipbook Based on the Addie Model in Science Learning for Elementary School Students - Yuliani Rahmawati; Komariah Komariah; Dede Trie Kurniawan (International Journal of Learning and Instruction (IJLI), 2022)
This study is motivated by the lack of use of technology-based media in elementary schools. With the aim of knowing student learning outcomes after using the flipbook the characteristics of living things and user responses. The research was conducted to describe flipbook analysis, design, development, implementation, user response, student learning outcomes and evaluation of flipbook characteristics of living things. Flipbook is a form of presentation of book learning media in virtual form. The method used in this research is D&D (design and development) and used the ADDIE model (analyze, design, development, implementation, and evaluation)). The findings when research students have never learned to use design technology are made in Canva for development into an android application, tested for feasibility by media, language, material, learning experts with very decent category results with an average score of 82.6%. The implementation was carried out achieved a very good response from users with an average of 88.9% and the average student learning outcomes increased as seen from an average of 32.6 to 73.8. After the flipbook was tested, many evaluations had to be done, such as suggestions from students, namely the volume of the audio sound was still small and relatively inaudible when used if there were other students speaking so that their voices clashed. In general, this flipbook of the characteristics of living things is appropriate for third grade students in elementary school.Â Keywords: Flipbook, Characteristics of Living Things, Elementary School